2008
DOI: 10.1002/pola.22524
|View full text |Cite
|
Sign up to set email alerts
|

Thermoreversible covalent crosslinking of maleated ethylene/propylene copolymers with diols

Abstract: The objective of this study is the thermoreversible crosslinking of maleated ethylene/propylene copolymer (MAn‐g‐EPM) using the equilibrium reaction with diols. Covalent hemi‐ester crosslinks are formed via the reaction of anhydrides with alcohols, while an equilibrium shift at elevated temperatures may result in their removal. High conversions to hemi‐ester are obtained at low temperatures in the presence of p‐toluenesulfonic acid, whereas conversions are low at high temperatures. The presence of microphase‐s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 28 publications
1
33
0
Order By: Relevance
“…No significant differences were observed in the FTIR spectra of (many) different samples taken from the reaction product, which suggests that the gelation does not result in non-homogeneous materials. The reaction of the cyclic anhydride groups with the alcohol functionalities does not occur in solution even in the presence of a catalyst [24], so no gelation occurs in solution for the 1 eOH, 2 eOH, OHeOH and 3 eOH crosslinkers. Cross-linking only occurs after solvent evaporation and is catalyzed by a suitable catalyst ( p-toluenesulfonic acid) for the diol (OHeOH cross-linker) [24] or by the amine groups [19] for the reactions with the 1 eOH, 2 eOH and 3…”
Section: Cross-linking Of Man-g-epmmentioning
confidence: 99%
See 3 more Smart Citations
“…No significant differences were observed in the FTIR spectra of (many) different samples taken from the reaction product, which suggests that the gelation does not result in non-homogeneous materials. The reaction of the cyclic anhydride groups with the alcohol functionalities does not occur in solution even in the presence of a catalyst [24], so no gelation occurs in solution for the 1 eOH, 2 eOH, OHeOH and 3 eOH crosslinkers. Cross-linking only occurs after solvent evaporation and is catalyzed by a suitable catalyst ( p-toluenesulfonic acid) for the diol (OHeOH cross-linker) [24] or by the amine groups [19] for the reactions with the 1 eOH, 2 eOH and 3…”
Section: Cross-linking Of Man-g-epmmentioning
confidence: 99%
“…MAn-g-EPM was partially (around 50%) or fully hydrolyzed via exposure to water from air for prolonged time at room temperature prior to the modification reactions with cross-linkers containing one or two 3 amine groups, respectively. For the modification with the OHeOH cross-linker, 5 mol% of p-toluenesulfonic acid, based on the molar amount of anhydride groups, was added to the solution as a catalyst [24]. Next, 0.5 mol of (di-functional) cross-linker per mol of grafted anhydride, was added to the solution, which was stirred for at least 30 min.…”
Section: Cross-linking Of Man-g-epmmentioning
confidence: 99%
See 2 more Smart Citations
“…More than 99% of azomethine bonds were hydrated in o10 min at ambient temperature. Mee et al 76 reported thermoreversible covalent crosslinking of maleated ethylene/propylene copolymers with diols (Scheme 21). Covalent hemi-ester crosslinks were formed via the reaction of anhydride side chains and diol linkers.…”
Section: Scheme 15mentioning
confidence: 99%